The rules general of treasury and their influence on the management of the public funds - Torres-Munguia, Nery L (2023)
Objective. Determine the relationship that exists between the level of application of general rules of treasury and the management of the public funds in the Provincial Municipality of Ambo, Huánuco (Peru), period 2020, the which, during agood management, could reconcile and have a good balance between its income and expenses. Methods. A quantitative, explanatory and crosssectional study was carried out. The population was represented by 65 employees public of theProvincial Municipality of Ambo. It employed as technique the survey quantitative and as instrumenta an sheet of collection of data surveys and to ensure the validation and reliability of the instrument was counted with a study pilot between employees and the judgment of experts in the field, respectively. To evaluate the association between the variables was applied correlation of Pearson's; likewise, was worked with a level of confidence of the 95 %, that is considered highly feasible; The level of significance established were a value of p < 0,01, minor to 0,05. Results. The result of the compliance of the rules of treasury general and their influence on the management of funds public was of the 74,06 %. The findings showed that the application of these rules has a level of compliance in unit of box of the 62,60 %. Meanwhile, the management of bank accounts and subaccounts show that the 83.33% of the answers were affirmative, while that in the use of the fund fixed for the box small is observed a compliance of the 93,33 %; in relation with the rules specific and the conciliation of sub accounts bank of the treasury public, we can say that the level compliance was of the 43,78 %, which indicates that they are statistically significant. Conclusion. It has been shown that the application of the general rules of treasury exerts influence on the management ofpublic funds of the Municipality, and that during a good management it will be able to reconcile and have a good balance between its income and expenses. In the same way, with a correct application and improvement in the perception of the rules, there will be a better perspective of the approach of control and the administration of the resources economic in the institution.